La geografía de los recursos naturales en Cuba: potencial natural y combinaciones territoriales - Ana María Luna Moliner (Investigaciones Geográficas, 1999)
This paper deals with the synthetic image of the regional distribution of natural resources in the island of Cuba, concealing different methodological approaches. Two theoretical assumptions were considered for this research, one related to the "natural potential" of the space, and the other concerning the "territorial combination of natural resources", both derived from the Russian School of Geography. The contribution of this study is two-fold: first, it gives a synthetic overview of the natural resources of Cuba, as a result of a research procedure that can easily be applied to any given territory: this global vision of natural resources is usually examined separately in other papers Second, a new methodological approach, whose practical application can be adopted universally, is also proposed.